Ageing John Banville: from Einstein to Bergson / O Tempo em John Banville: de Einstein a Bergson - Nicholas Taylor-Collins (ABEI Journal, 2020)
Abstract: There is a clear engagement with theories of time across Banville’s oeuvre, from his earliest published work through to the twenty-first-century novels. I explore how, in their engagement with age and ageing, Banville’s characters adopt and interrogate Albert Einstein’s and Henri Bergson’s competing ideas of the present and the passage of time, sliding from favouring the former to prioritising the latter. Martin Heidegger’s conception of Dasein, a Being-toward-death, allows me to explore how Banville’s characters evoke either Einstein’s spacetime and series of nows, or Bergson’s psychologised Duration (Durée). This is borne out in Gabriel Godkin’s subverted and anti-atavistic narrative in Birchwood (1973), the battle over authenticity between Copernicus and Rheticus in Doctor Copernicus (1976), and how Hermes controls the mortals’ time and tries his best to age in The Infinities (2009). I conclude that Banville’s characters’ evolving preference for Bergsonian over Einsteinian tropes indicates an acceptance and happy engagement with the ageing process.